THE IMPACT OF FINANCIAL DEVELOPMENT ON CARBON EMISSIONS: AN ASEAN PERSPECTIVE - NA, Muhammad Firdaus Al Farohi; Muhammad Zaky Nur Fajar; Muhammad Jamie Rofie Quality (Journal of Central Banking Law and Institutions, 2024)
The global discourse surrounding the climate crisis has intensified in recent years, leading to various international agendas of global and regional bodies. Notably, ASEAN, characterised by its rapid development, has emerged as a significant contributor to CO2 emissions. Therefore, this study seeks to explore the relationship between financial development and CO2 emissions using the data of nine ASEAN countries from 2000 to 2020. Recognizing the multidimensional nature of financial development, the analysis divides financial development to two distinct indices, FM and FI. This study uses panel data ARDL with the PMG estimation used after testing all the outcomes. The analysis found non-significant effects of financial development on carbon emissions using various estimation techniques. However, separating into FI and FM yields insightful results. While the effect in the short run is unclear, FI increases the carbon emission in the long run by 1.17 percent of each one percent increase, proving that financial institutions in the current state promote an unsustainable effect on the environment. This effect occurs because they drive demand towards energy consumption while also expanding more environmentally harmful sectors. The error correction term signifies that the adverse effect of financial institutions takes approximately six years. These findings underscore the importance of integrating sustainability into development of the financial sector and advancing its maturity by enhancing access to financial institutions and markets to reduce the adverse effect of the climate crisis.